OUTCOME AND TOXICITY OF EXTENDED-FIELD INTENSITY MODULATED RADIOTHERAPY (EF-IMRT) IN LOCALLY ADVANCED CARCINOMA OF CERVIX – EXPERIENCE FROM TERTIARY CANCER CENTER - ANJAN BERA; AVIK MAJI; DEBJANI BANERJEE; DEBOJYOTI MANNA; SHILPI ADHIKARY (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Whether to irradicate the para-aortic node prophylactically or not in locally advanced cervical carcinoma in the absence of para-aortic lymphadenopathy, the recommendation varies across guidelines. Extended field radiotherapy may improve overall survival (OS) by better local control of the para-aortic nodal region compared to pelvic RT alone, especially in patients unable to tolerate concurrent pelvic chemoradiotherapy. Methods: This was a single institutional retrospective study carried out in the department of radiotherapy at NRSMCH, Kolkata. A total of 30 HPE-proven locally advanced cervical cancer patients treated with extended field intensity-modulated radiotherapy (IMRT) were selected for this retrospective study. Results: Response assessment was done 12–16 weeks after completion of treatment and 26 patients (86%) had complete locoregional responses and four patients had the local disease (14%). The 2-year OS was 86%. The common toxicity was Grade I small bowel toxicity (diarrhea), skin reactions, and Grade I neutropenia, seen in 78%, 63%, and 58% of patients, respectively. Another acute toxicity was Grade I anemia seen in 35% of patients. The common late toxicity was Grade I lower GI (11%). Conclusions: Extended Field-IMRT is a convenient, feasible, and effective treatment modality for target coverage and para-aortic nodal control with minimal toxicity.